THE INTERNAL AUDIT PROCESS IN COOPERATIVES: EXAMPLE OF EĞİRDİR AGRICULTURAL DEVELOPMENT COOPERATIVES (Third Sector Social Economic Review, 2020)
Cooperatives which are formed by individuals who voluntarily gather their economic powers up to achieve works that can not be done (carried out) individually are important gear in global economic factory. These organizations are controlled through internal audits which are conducted by general assemblies, board of managers and their shareholders to check whether they are protected against all kinds of irregularities and whether their activities are carried out in accordance with the legislation. In order to make an effective control in cooperatives, especially board of supervisors should be conscious and educated. The main purpose of this study is to contribute to the internal audit process to be a more effective mechanism by bringing solutions to the disruptions in the internal audit process through examining internal audit in terms of laws, regulations and operation in the cooperatives.
Keywords: Cooperative; Audit; The Internal Audit